2009
DOI: 10.1143/jjap.48.117001
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Structural Analyses of KOH Activated Carbon from Waste Coffee Beans

Abstract: The relationship of the detailed structural change of KOH activated carbon and hydrogen storage ability was investigated in activated carbon materials fabricated from waste coffee beans. The specific surface area of porous carbon materials calculated from N 2 adsorption isotherms stood at 2070 m 2 /g when the weight ratio of KOH to carbon materials was 5 : 1, and pore size was in the range of approximately 0.6 to 1.1 nm as micropores. In the structural analysis, X-ray diffraction analysis and Raman spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…In activated carbon chromium ions adsorption increases from 0.1 to 0.3 g and after that it starts decreasing because the number of availability of the exchangeable binding sites for adsorption decreases (Murugesan et al 2012). Figure 5a-e shows the FTIR spectrum of CMC (Rachtanapun and Rattanapanone 2011; Saputra et al 2014), biopolymeric gel beads (Dewangan et al 2011) and activated carbon (Hesas et al 2013;Takahata et al 2009). The distinct difference is observed between CMC, bio-polymeric gel beads and activated carbon.…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 99%
See 1 more Smart Citation
“…In activated carbon chromium ions adsorption increases from 0.1 to 0.3 g and after that it starts decreasing because the number of availability of the exchangeable binding sites for adsorption decreases (Murugesan et al 2012). Figure 5a-e shows the FTIR spectrum of CMC (Rachtanapun and Rattanapanone 2011; Saputra et al 2014), biopolymeric gel beads (Dewangan et al 2011) and activated carbon (Hesas et al 2013;Takahata et al 2009). The distinct difference is observed between CMC, bio-polymeric gel beads and activated carbon.…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 99%
“…Due to the lack of crystallinity, metal ions could easily penetrate into the gel beads and hence increase in adsorption capacity occurs (Yang et al 2011). The diffraction peak at the position of 2θ = 23° shows the amorphous region of the activated carbon because KOH activation increases the specific surface area of porous carbon materials and decreases the crystallinity of the structure (Takahata et al 2009).…”
Section: Xrd Analysismentioning
confidence: 99%
“…Furthermore, the hydrogen storage mechanism should involve physical adsorption to enable repeated use of hydrogen storage equipment. High specific surface areas are required for high-efficiency physical adsorption of hydrogen [2]. Light weight is also necessary for these storage materials to ensure low energy consumption during transport.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, some reports indicated that the activated carbon having large specific surface area adsorbed 0.6-1.3 wt.% of hydrogen at room temperature. [2,4]. It is known that porous carbon materials with a high specific surface area can be prepared by chemical activation with metallic compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation